Applied Digital Humanities: Calling for a more engaged Digital Humanities - Glawion, Anastasia; Lang, Sabine; Kremer, Dominik; Mahlberg, Michaela; Wagner, Andreas (Digital Humanities im deutschsprachigen Raum (DHd), 2025)
Keywords: Applied Digital Humanities; engagement

Co-creation of Place-Based Content for Field Trips and Public Trails by Geo-Content Management - Kremer, Dominik; Wagner, Andreas (Transforming Places. Proceedings of the 4th International Symposium on Platial Information Science (PLATIAL’23), 2023)
While learning about places in classrooms takes large profit of digital geomedia, digital assisted learning on site is still bound to fragmented solutions, as innovative Extended Reality immersions often demand too much resources to be run on average smartphones. In addition, efforts staging digital aided learning experiences on site are still too cumbersome for regular teaching. In an explorative answer to this challenge, we introduce the FAU Geoexplorer, aiming at focussed presentation of geomedia on site supported by an easy to follow content creation process.<br
Keywords: location-based services; field-trips; geodidactics

Der GeoExplorer: ein Werkzeug für die Gestaltung ortsbezogener digitaler Lernerfahrungen - Kremer, Dominik; Feulner, Barbara; Wagner, Andreas (GW-Unterricht : eine Zeitschrift des "Forums GW - Verein für Geographie und Wirtschaftserziehung", 2025)
Lernen vor Ort fördert das Erschließen räumlicher Muster. Gleichzeitig liefern Geomedien am Standort Zusatzinformationen und ermöglichen den Vergleich einzelner Standorte. Der Aufwand für die Einarbeitung und Vorbereitung digital unterstützter Lernsituationen durch Apps ist weiterhin hoch. Am Beispiel der freien Anwendung GeoExplorer zeigen wir, wie eine gezielte Unterstützung des Eingabeprozesses nicht nur die Aufwände senkt, sondern auch die Vor-Ort-Erfahrung strukturiert, und stellen zwei Szenarien für den Einsatz an Schulen vo
Keywords: Mobiles ortsbezogenes Lernen; Exkursionen; (digitale) Geomedien; Co-Creation

Prototyping an Atlas of Early Modern English Drama: An Experiment on DraCor Data - Giovannini, Luca; Wagner, Andreas (AIUCD 2025: Diversità, equità e inclusione (AIUCD 2025), 2025)
This short contribution leverages the recently released English Drama Corpus from the DraCor project (Fischer et al. 2019) to create an interactive map of geographical references in early modern English drama by means of Named Entity Recognition (NER) tools. The prototype allows to visualise interesting patterns in the playwrights’ use of locations while underscoring the need of improved NLP tools to effectively tackle geospatial research questions about early modern literatur
Keywords: early modern drama; spatial humanities; geocoding; digital cartography